2019
DOI: 10.31557/apjcp.2019.20.10.3037
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mouse Double Minute 2 -309T>G Polymorphism with Acute Myeloid Leukemia in an Iranian Population: A Case- Control Study

Abstract: Background: Genetic factors play a substantial role in acute myeloid leukemia (AML) etiology. Overexpression of the mouse double minute 2 (MDM2) gene has been explored in many tumors. However, the role of MDM2-309T>G (rs2279744) polymorphism in AML remains unclear. We have performed this study to examine the association of MDM2-309T>G with AML in an Iranian population. Methods: We have examined the association of N MDM2-309T>G polymorphism in 73 cases diagnosed with AML and 80 healthy controls by tetra-primer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Regarding the risk for AML, Soleymannejad M et al [24] noticed an association between MDM2 rs2279744 and AML susceptibility. Also, Phillips CL et al [25] reported the same association on childhood AML patients and no association with treatment response [25].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the risk for AML, Soleymannejad M et al [24] noticed an association between MDM2 rs2279744 and AML susceptibility. Also, Phillips CL et al [25] reported the same association on childhood AML patients and no association with treatment response [25].…”
Section: Introductionmentioning
confidence: 99%